ANALYSIS OF STUDENTS' MATHEMATICS LEARNING DIFFICULTIES CLASS V ELEMENTARY SCHOOL HERA - Ilda Guterres, Angela Freitas Diogo Savio (JURNAL ILMU PENDIDIKAN, 2026)
This study aims to determine students' difficulties in learning mathematics and the factors that contribute to their difficulties. This study used a qualitative approach with a descriptive qualitative research method intended to describe students' difficulties in learning mathematics. The subjects were ten students in grade V EBC 3.theciclo Hera. The results of this study indicate that the tendency of difficulties experienced by students is conceptual difficulties, where students do not fully understand the concept of fractions, students have difficulty determining the numerator and denominator, reversed in writing fractional values, and difficulty distinguishing the symbols more than „>‟ and less than ‟<‟. The factors that make students have difficulty learning mathematics are low student attitudes and interests, where students do not like mathematics lessons which make students not pay attention to the teacher during mathematics lessons so that students feel unmotivated during mathematics lessons.